Analisis Pengaruh Endorser Credibility pada Brand Equity dan Minat Beli Konsumen - Dewantoro, Reza Rizky; Adidarma, Wijaya (Journal of Entrepreneurship, Management and Industry (JEMI), 2019)
The appeal of an advertisement is measured whether it can attract the attention of the viewers or not. For this purpose, TOP instant coffee uses a credible endorser to advertising its brand. This study is aimed to analyze the influence of the endorser’s credibility on brand equity and purchase intention. This research involved 162 respondents those are instant coffee lovers. The result found that the endorser credibility has positive impact on brand equity, but there’s only one aspect that influence brand equity, that is trustworthiness. Other aspects of endorser’s credibility partially influence brand equity. Endorser credibility also has positive impact on purchase intention, but only for one aspect, that is trustworthiness. Others aspects those are attractiveness and expertise have no effect on purchase intention. Brand equity also influence positively on purchase intention. Three aspects of brand equity including perceived quality, brand awareness and brand loyalty have significant effect on purchase intention, however only brand association that has no effect on purchase intention. The appeal of an advertisement is measured whether it can attract the attention of the viewers or not. For this purpose, TOP instant coffee uses a credible endorser to advertising its brand. This study is aimed to analyze the influence of the endorser’s credibility on brand equity and purchase intention. This research involved 162 respondents those are instant coffee lovers. The result found that the endorser credibility has positive impact on brand equity, but there’s only one aspect that influence brand equity, that is trustworthiness. Other aspects of endorser’s credibility partially influence brand equity. Endorser credibility also has positive impact on purchase intention, but only for one aspect, that is trustworthiness. Others aspects those are attractiveness and expertise have no effect on purchase intention. Brand equity also influence positively on purchase intention. Three aspects of brand equity including perceived quality, brand awareness and brand loyalty have significant effect on purchase intention, however only brand association that has no effect on purchase intention. Keywords: Credibility Endorser, Brand Equity, Purchase Intention